2018
DOI: 10.1111/peps.12307
|View full text |Cite
|
Sign up to set email alerts
|

General mental ability, conscientiousness, and the work–family interface: A test of mediating pathways

Abstract: This study proposed a model in which employee general mental ability (GMA) and conscientiousness are linked to work–family conflict and enrichment through their relationship with occupational prestige and coping styles. We evaluated this model in a sample of 709 working adults from the National Survey of Midlife Development II in the United States. Results indicate that, through occupational prestige and subsequent psychological job demands and financial well‐being, GMA was related to work‐to‐family conflict (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 142 publications
(192 reference statements)
1
11
0
Order By: Relevance
“…Likewise, job resources of autonomy and task significance lead to job satisfaction, which is found to be beneficial for WFE (Chen et al, 2017). Additionally, Huang et al (2019) found that occupational prestige influenced WFE through an increase in autonomy. In the family domain, family support generates feelings of family satisfaction resulting in FWE (Siu et al, 2015).…”
Section: Family Factorsmentioning
confidence: 93%
See 3 more Smart Citations
“…Likewise, job resources of autonomy and task significance lead to job satisfaction, which is found to be beneficial for WFE (Chen et al, 2017). Additionally, Huang et al (2019) found that occupational prestige influenced WFE through an increase in autonomy. In the family domain, family support generates feelings of family satisfaction resulting in FWE (Siu et al, 2015).…”
Section: Family Factorsmentioning
confidence: 93%
“…Butler et al, 2005;Mauno and Rantanen, 2013;Presti and Mauno, 2016), decision latitude (Grzywacz and Marks, 2000), autonomy (e.g. Grzywacz and Butler, 2005;Rastogi et al, 2016;Salehi et al, 2015;Voydanoff, 2004) and skill discretion (Baral and Bhargava, 2011a;Butler et al, 2005;Carlson et al, 2011a, b) (2) Increase in skill level/variety (Baral and Bhargava, 2011a;Butler et al, 2005), learning opportunities (Voydanoff, 2004), meaningful work (Voydanoff, 2004), respect, occupational prestige (Huang et al, 2019;Voydanoff, 2004), job security (Carlson et al, 2011a, b), time adequacy (Lingard et al, 2010) (3) Reduction in work demands (Butler et al, 2005;Jain and Nair, 2019), workload (Ghislieri et al, 2017a, b), work time pressure (Brosch and Binnewies, 2018;Voydanoff, 2004), organization time demands (Wayne et al, 2006)…”
Section: Antecedents Of Work-family Enrichmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, practical recommendations concentrate on organizational work-family initiatives which show mixed results (Ollier-malaterre, 2010). As personal dispositions entail subjective assessment and reactions to situations (Friede and Ryan, 2005), they represent a sense of personal agency that helps navigate through the work-family interface (Haines et al, 2013;Huang et al, 2019). Thus, studying personality dispositions and the work-family experiences not only provides a better understanding of these relationships but also offer supplementary ways to deal with the interface (Allen et al, 2012;Michel and Clark, 2013).…”
Section: Introductionmentioning
confidence: 99%